Influence of Various Nutrient Media on the Seed Germination, Growth and Development of Acacia (Acacia Auriculiformis L.) - Jamali, Ali Raza; Jamali, Shamshad; Kaleri, Asif Ali; Soomro, Abdul Wahab; Magsi, Shuaib Ahmed; Hajano, Asif Ali; Kalhoro, Hussain Bakhsh; Jamali, Muzamil Farooque (Journal of Agriculture and Veterinary Science, 2024)
The present research was carried out in 2022-23 at the SAU Nursery, Sindh Agriculture University, Tandojam, Pakistan. To assess the influence of various Nutrient Media on seed germination growth and development of Acacia (Acacia auriculiformis L.) The experimental trial was carried out in Completely Randomized Design (CRD) with three replications. Acacia seeds were grown in Nutrient Media comprising canal silt, farmyard manure, rice husk and dry leaves in (1:1) among the nutrient media comprising canal silt + Rice husk (1:1) has shown the best result in germination and growth parameters. Viz germination (83.33%), plant height (17.70cm), number of branches plant-1 (27.66), fresh biomass of shoot (30.27g), dry biomass of shoot (14.15g), and quality index (0.78) while the poor results was recorded in canal silt germination (23.33%), Based on Nutrient Media, NM3 canal silt + Rice husk (1:1) performed better germination growth and development of Acacia, the present study that the Nutrient MediaNM3 =canal silt + rice husk (1:1) had better result for all parameters. It has been suggested that Acacia may be nourished with Nutrient Media Canal Silt + Rice husk (1:1) and also good in Canal silt + Dry leaves (1:1).
Keywords: Rice husk; Dry leaves; Germination; Farmyard manure; Quality index